Monitoring of Flexible Support Effects Using the Responses of Multi-span Bridges via Wavelet Transform - BASU, BISWAJIT; NGUYEN, DINH VAN (My University, 2012)
In this paper the temporal and spectral effects of the flexible support on the response of multi-span bridges subjected to spatially-varying differential support motions are investigated by using wavelet transform. The Modified Littlewood-Paley wavelet basis is used for the analysis. In the case study of a two-span bridge, the spatially-varying earthquake motions at support bases are simulated. Two finite element-based models of the bridge, the rigid-base support model that assumes rigid soil from the foundation beds, and the flexible-base mid-support model accounting for actual soil stiffness, are analysed. In addition to shortening structural vibration period and amplifying the response amplitude, the flexible base is found to act as a time delay operator to the bridge responses
The 6th European Workshop on Structural Health Monitoring (EWSHM)
PUBLISHED
Dresden, Germany
Keywords: Health monitoring; multi-span bridges; earthquake excitations; wavelet transform